2013
DOI: 10.4103/0300-1652.108890
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to utilisation of maternal health services in a semi-urban community in northern Nigeria: The clients′ perspective

Abstract: Background:Low level of utilisation of maternal health services is a major factor responsible for high maternal mortality in northwestern region of Nigeria. This study was aimed at determining the barriers to utilisation of maternal health services from the perspective of mothers in northwestern Nigeria.Materials and Methods:A cross-sectional study of 150 mothers, selected through multistage technique, was conducted. Data were collected using a structured interviewer-administered questionnaire, and analysed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
119
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(136 citation statements)
references
References 14 publications
12
119
5
Order By: Relevance
“…Non past complications and negative Researchers andReviewers, 2006-2017: www.afrrevjo.net. Indexed African Journals Online: www.ajol.info provider attitude were reasons mothers gave for non utilization of maternal health services in northwestern Nigeria (Idris et al, 2013). Poor health seeking behaviours in terms of low antenatal care use, postnatal care use, and skilled birth attendant at delivery exist in rural Nigeria (Osubor, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Non past complications and negative Researchers andReviewers, 2006-2017: www.afrrevjo.net. Indexed African Journals Online: www.ajol.info provider attitude were reasons mothers gave for non utilization of maternal health services in northwestern Nigeria (Idris et al, 2013). Poor health seeking behaviours in terms of low antenatal care use, postnatal care use, and skilled birth attendant at delivery exist in rural Nigeria (Osubor, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In another baseline survey by UNFPA of UNFPA Assisted States in Nigeria, the proportion of women who delivered in a health facility was found to be high in Anambra (87.9%), Abia (82.8%), Osun (76.4%) and Ogun (74.2%) states, while in Sokoto (5.7%), Kebbi (8.2%) and Katsina (7.5%) states, the proportions were extremely low (UNFPA, 2010). Furthermore, a cross-sectional study carried out among women in a semi-urban settlement in Giwa, Northwestern Nigeria revealed that majority (76%) of the women had their deliveries at home and were not supervised by skilled personnel (Idris et al, 2013), while another study of women attending antenatal care at the Usmanu Danfodiyo University Teaching Hospital Sokoto showed that despite the fact that these women received antenatal care at the Tertiary Institution, 31.5% delivered elsewhere and majority (15.3%) of the deliveries elsewhere took place at the woman's home (Ekele and Tunau, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A 1991 national study found that most Muslim participants followed the religious injunction to procreate with a prevailing belief that children constitute a continuous flow of gifts from divine providence, and, as such, none should be refused 12 . Focus group discussions conducted with men and women in 2007 and 2013 showed that in Kano State, for example, this very literal interpretation of the scriptures still prevailed [13][14][15] . People wanted to have many children also so that their lineage is continued and their prestige improves.…”
Section: Demand For Family Planning Servicesmentioning
confidence: 99%
“…Couples in northern Nigeria desire many children, and therefore do not wish to use contraception [12][13][14][15] . Several religious and cultural norms contribute to this phenomenon.…”
Section: Demand For Family Planning Servicesmentioning
confidence: 99%